(untitled) (Training and Practice : Journal of Educational Sciences, 2017)
In 1868 Physical training became compulsory by the law in the training-college. In the beginning the material was based on the German physical exercise, which was continuously expanded for instance with the practice times, games, swimming and athletic exercises. In 1973 there was a significant change in the practical training of Physical Education, the special course was introduced. First it was named as special college, but it was changed to cultural domain training, in which students could acquire theoretical and practical subjects, which were essential for the teaching of Physical Education. The requirements of the teaching-college will be changed in September, which will have an effect on the subjects of Physical Education as well.